Lymphatic embolization for the management of symptomatic pelvic lymphocele after radical prostatectomy with lymph node dissection: Report of two cases. Issue 1 (7th October 2020) - Schneider, Gregoire; Ourfali, Said; Rouviere, Olivier; Pagnoux, Gaele; Colombel, Marc
Abstract : Introduction: Pelvic lymphocele is the most common complication of pelvic lymph node dissection after radical prostatectomy. Management of symptomatic pelvic lymphocele begins with percutaneous drainage, followed by sclerotherapy or surgical marsupialization and more recently, lymphatic embolization. In this article, we show the feasibility and results of two lymphatic embolization after prostatectomy with lymph node dissection. Case presentation: We decided to perform lymphatic embolization in two patients with persistent symptomatic pelvic lymphocele, after percutaneous drainage. This was done through inguinal lymph node puncture using Lipiodol and N ‐butyl cyanoacrylate glue injection. Drainage removal was done on the day after the procedure and clinical recovery was maintained at follow‐up visits, 3 and 4 months later, in both patients. Computed tomography at 6 and 10 weeks after embolization showed the disappearance of the lymphocele. Conclusion: Our two case reports support the promising results of lymphatic embolization in this pathology.